2014
DOI: 10.1039/c3lc51334c
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput device for size based separation of C. elegans developmental stages

Abstract: Caenorhabditis elegans is a widely used model organism to study development, aging and behavior. Many of these biological studies require staging a large number of worms to assay a synchronized population of animals. Conventional synchronization techniques such as manual picking, gravity stratification and chemical bleaching are labor-intensive and could perturb animals’ physiology. Thus, there is a need for a simple inexpensive technology to sort a mixed population of worms based on their developmental stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…The success rate could be further enhanced through (i) addressing the issues of micropipette clogging and pipette-worm body misalignment and (ii) more accurate on-chip size synchronization method of the loaded worms using a microfluidic device integrated with computer vision algorithms for automatic worm sizing. 33,38,56 The current worm injection system is more suitable for drug testing/screening applications (in which drug/chemical solutions need to be injected into the worm body); 20,25 however, it is still challenging for the system to perform microinjection of the worm gonad for creating transgenic C. elegans due to the following reasons. The microfluidic device uses a narrow channel to immobilize a C. elegans worm, and the compressed worm body makes the visual identification of the gonad difficult.…”
Section: B Characterization Of Worm Injection Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The success rate could be further enhanced through (i) addressing the issues of micropipette clogging and pipette-worm body misalignment and (ii) more accurate on-chip size synchronization method of the loaded worms using a microfluidic device integrated with computer vision algorithms for automatic worm sizing. 33,38,56 The current worm injection system is more suitable for drug testing/screening applications (in which drug/chemical solutions need to be injected into the worm body); 20,25 however, it is still challenging for the system to perform microinjection of the worm gonad for creating transgenic C. elegans due to the following reasons. The microfluidic device uses a narrow channel to immobilize a C. elegans worm, and the compressed worm body makes the visual identification of the gonad difficult.…”
Section: B Characterization Of Worm Injection Performancementioning
confidence: 99%
“…The pumping rate ranges in 240-280 pumps/min for both groups and is in good agreement with values reported in the previous studies on the wild-type N2 worms. 33 This indicates that the microfluidic device and the automated robotic injection are less likely to induce adverse effects on the physiological condition of the injected C. elegans.…”
Section: Post-injection Viability Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus microfluidic systems are used as a platform for various studies with C. elegans. [20][21][22][23][24][25][26][27][28] McCormick et al demonstrated a microfluidic device for analysis of C. elegans orientation. 29 They designed the device in order to immobilize C. elegans and only allow the movement of the head of C. elegans.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in microfluidics and microsystems [6][7][8][9][10][11][12][13][14] have further facilitated investigation into C. elegans' behavior patterns in response to controlled external stimuli. Enabled by state-of-the-art technologies, a variety of external stimuli has been independently studied as a variable in the worm's environment, including temperature, [15][16][17] chemicals, [18][19][20][21] food-related signals, 22 gas concentration, 23 electric field, 24,25 and physical obstacles.…”
Section: Introductionmentioning
confidence: 99%